Exploring health literacy development in parents of children with significant disabilities through an ecological systems and experiential learning framework - Fiala, Maryjan M. (My University, 2026)
Parents of children with significant disabilities frequently assume primary responsibility for delivering and coordinating complex in-home care. These responsibilities often require parents to develop advanced levels of health literacy through a combination of professional-mediated education and self-directed experiential learning. Despite this role, parents remain an understudied population within adult learning and health literacy scholarship. Grounded in ecological systems theory and experiential learning theory, this qualitative study explored how parents describe learning from encounters within complex systems (e.g., health care, education) in the context of caregiving. Data were collected from a heterogenous sample of 18 parents through in-depth, semi-structured interviews at two time points. Parents reported providing care for children with diverse diagnoses (e.g., Down Syndrome, traumatic brain injury, cerebral palsy, fetal alcohol syndrome) and multiple co-occurring conditions. The following interconnected findings were identified through thematic analysis: parents approached caregiving with full biographies but often limited prior knowledge of disability and medical complexity, caregiving disrupted their expectations for parenting, they engaged in ongoing efforts to make experiences intelligible when encountering the limits of their prior knowledge, and they described learning from caregiving experiences as distinct but inseparable from parenting. These findings challenge frameworks that treat health literacy as a discrete competency, suggesting instead, that for these parents, health literacy development was, by necessity, part of parents’ ongoing biographical development.
Keywords: Adult learning; Health literacy; Caregiving; Ecological systems; Experiential learning; Children with special health care needs